Exercises in probability : a guided tour from measure theory to random processes, via conditioning - Chaumont, L. (Loic); Yor, Marc. (Cambridge : Cambridge University Press, 2012)
'Derived from extensive teaching experience in Paris, this second edition now includes over 100 exercises in probability. New exercises have been added to reflect important areas of current research in probability theory, including infinite divisibility of stochastic processes, past-future martingales and fluctuation theory. For each exercise the authors provide detailed solutions as well as references for preliminary and further reading. There are also many insightful notes to motivate the student and set the exercises in context'--
Includes bibliographical references (p. 270-277) and index.
Keywords: Probabilities; Probabilities -- problems, exercises, etc; MATHEMATICS / Probability & Statistics / General